Gibberellin is not a regulator of miR156 in rice juvenile-adult phase change - Tanaka, Nobuhiro (Rice (N Y), 2012)
Plant hormone gibberellin (GA) promotes juvenile-adult phase change in higher plants. To confirm the functions of GA in rice, I used dwarf mutant d18-dy. d18-dy is a loss-of-function allele of D18, which encodes GA3ox2. d18-dy mutant exhibited long juvenile phase in morphological traits such as the size of the shoot apical meristem (SAM), shape of leaf blades, presence or absence of midribs and node–internode differentiation in stem. In contrast, expression patterns of juvenile-adult phase change markers miR156 and miR172 were similar between wild type and d18-dy. In addition, d18-dy mutation and GA did not affect expression levels of downstream genes of miR156. GA does not function upstream of miR156 in juvenile-adult phase change. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1939-8433-5-25) contains supplementary material, which is available to authorized users.